Immunization with M2e-Displaying T7 Bacteriophage Nanoparticles Protects against Influenza A Virus Challenge - Hashemi, Hamidreza; Pouyanfard, Somayeh; Bandehpour, Mojgan; Noroozbabaei, Zahra; Kazemi, Bahram; Saelens, Xavier; Mokhtari-Azad, Talat (PLOS ONE, 2012)
Considering the emergence of highly pathogenic influenza viruses and threat of worldwide pandemics, there is an urgent need to develop broadly-protective influenza vaccines. In this study, we demonstrate the potential of T7 bacteriophage-based nanoparticles with genetically fused ectodomain of influenza A virus M2 protein (T7-M2e) as a candidate universal flu vaccine. Immunization of mice with non-adjuvanted T7-M2e elicited M2e-specific serum antibody responses that were similar in magnitude to those elicited by M2e peptide administered in Freund’s adjuvant. Comparable IgG responses directed against T7 phage capsomers were induced following vaccination with wild type T7 or T7-M2e. T7-M2e immunization induced balanced amounts of IgG1 and IgG2a antibodies and these antibodies specifically recognized native M2 on the surface of influenza A virus-infected mammalian cells. The frequency of IFN-γ-secreting T cells induced by T7-M2e nanoparticles was comparable to those elicited by M2e peptide emulsified in Freund’s adjuvant. Emulsification of T7-M2e nanoparticles in Freund’s adjuvant, however, induced a significantly stronger T cell response. Furthermore, T7-M2e-immunized mice were protected against lethal challenge with an H1N1 or an H3N2 virus, implying the induction of hetero-subtypic immunity in our mouse model. T7-M2e-immunized mice displayed considerable weight loss and had significantly reduced viral load in their lungs compared to controls. We conclude that display of M2e on the surface of T7 phage nanoparticles offers an efficient and economical opportunity to induce cross-protective M2e-based immunity against influenza A.